The Effect of Art Therapy on Children's Self-Concept - Hidayah, Rifa (Makara Human Behavior Studies in Asia, 2014)
The success of the child's social adjustment related to the concept of self. To improve self concept interventions among others through art therapy. The purpose of this study was to examine the effect of art therapy for children's self-concept. This study was conducted using experiments and involving 21 children. Experiment in the form of art therapy treatment by using images as the media, held for five sessions, each session lasting 90 minutes. Five sessions of art therapy implementation consists of (1) the session to know yourself, (2) I am among friends, (3) I am and my surroundings, (4) I am and the Indonesian people as well as (5) my goal. Method of data collection using self-concept scale and interviews were then analyzed by t-test. The results showed that art therapy is effective to increase in the child's self-concept. Thus, if the concept of a low child, the child immediately treated the art therapy to improve the concept itself.